2012
DOI: 10.1002/net.21476
|View full text |Cite
|
Sign up to set email alerts
|

Linearly many faults in arrangement graphs

Abstract: The star graph proposed by Akers et al. (Proc Int ConfParallel Process, University Park, PA, 1987, pp. 393-400) has many advantages over the n-cube. However, it suffers from having large gaps in the possible number of vertices. The arrangement graph was proposed by Day and Tripathi (Inf Process Lett 42 (1992), 235-241) to address this issue. Since it is a generalization of the star graph, it retains many of the nice properties of the star graph. In fact, it also generalizes the alternating group graph (Jwo et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 31 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…Chiang and Chen [4] showed that is isomorphic to the -alternating group graph . Recent years have witnessed the continued interest in the research of arrangement graphs [8], [9], [13], [17], [19], [24], [25].…”
Section: Index Terms-arrangement Graph Inclusion-exclusion Prinmentioning
confidence: 99%
“…Chiang and Chen [4] showed that is isomorphic to the -alternating group graph . Recent years have witnessed the continued interest in the research of arrangement graphs [8], [9], [13], [17], [19], [24], [25].…”
Section: Index Terms-arrangement Graph Inclusion-exclusion Prinmentioning
confidence: 99%
“…Proof. The eigenvalues of A(4, 3) and A(5, 3) are determined by a computer; these are {−3 [1] , −2 [6] , −1 [3] , 0 [4] , 1 [3] , 2 [6] , 3 [1] } and {−3 [14] , −2 [5] , −1 [12] , 1 [14] , 2 [6] , 4 [8] , 6 [1] }, respectively, which agree with the assertion. (Note that letting n = 4 in the assertion, the sum of the multiplicities of −3 and n − 7 equals 1.)…”
Section: Eigenvalues Of A(n 3) and A(n 4)mentioning
confidence: 99%
“…Many properties of arrangement graphs have been studied by a number of authors, see, e.g. [4,5,6,7,8,19,20].Another family of graphs with the same nature as the arrangement graphs are the derangement graphs.The n-derangement graph is a graph whose vertices correspond to all the permutations of [n] where two permutations are adjacent if they differ in all n positions. It is known that the eigenvalues of the derangement graph are integers (see [1,11,15,17]).…”
mentioning
confidence: 99%
“…For example, the spectra of arrangement graphs were studied in [2,7], the faulty tolerances were investigated in [36,39], and the conditional fault tolerance and the fault diagnosability were given in [40,41]. For more works on the arrangement graphs, we refer the reader to [2,8–12,19,19,23,31,38] and the references therein. These investigations show that this class of graphs admit many nice properties, such as hierarchical structure, simple shortest path routing, high connectivity, and so on.…”
Section: Introductionmentioning
confidence: 99%